Amizade, política e a produção de subjetividades éticas: sobre a construção do mundo contemporâneo como Amor Mundi - GONÇALVES, Lucidalva Pereira (2020)
This master’s thesis analyzes the intersubjective friendship phenomenon as an experience with a political potential, once free talk and sharing opinions enable a comunication between different discourses. It is a kind of practice where the world represents a privileged locus in human relationships, with subjectivities production and, consequently, the way of being oneself and other (s). According to Hannah Arendt, in political quality of friendship, it lies responsibility with a common world. However, in this perspective, the intersubjective experience in friends encounter, it is different from the kind of intimate relationships (defined by the molds of familiarity or fraternity), that characterized the intense privatization of public space in Modern Age. For this research construct, methodological character used is the bibliographic-qualitative method, employing a hermeneutic research model by understanding a procedure that recognizes human belonging to History as an inheritance that propagates subjectivities formation (and that allows to understand the meaning of friendship in its connection with tradition, by referring to the classic concept of Philía). On the other hand, it is also a phenomenological model when is conceiving friendship as a phenomenon, as it presents itself to the Conscience. This thesis is based on the philosophical and political theory of Hannah Arendt and on the specialized literature in friendship studies, with emphasis on Francisco Ortega and Lívia Godinho Nery Gomes. With Arendt, friendship is presented under the name of Philía Politique, and in its embryonic sense, it contemplates the dialogical relationship with the other and the belonging of humanity to the world that stands between men.